On welfare frameworks and catastrophic climate risks - Millner, Antony (Munich, 2013)
"Recent theoretical work in the economics of climate change has suggested that climate policy is highly sensitive to ‘fat-tailed’ risks of catastrophic outcomes (Weitzman, 2009). Such risks are suggested to be an inevitable consequence of scientific uncertainty about the effects of increased greenhouse gas concentrations on climate. Criticisms of this controversial result fall into three categories: The first suggests that it may be irrelevant to cost benefit analysis of climate policy, the second challenges the fat-tails assumption, and the third questions the behavior of the utility function assumed in the result. This paper analyses these critiques and suggests that those in the first two categories have formal validity, but that they apply only to the restricted setup of the original result, which may be extended to address their concerns. They are thus ultimately unconvincing. Critiques in the third category are shown to be robust however they open up new ethical and empirical challenges for climate economics that have thus far been neglected—how should we ‘value’ catastrophes as a society? I demonstrate that applying results from social choice to this problem can lead to counterintuitive results, in which society values catastrophes as infinitely bad, even though each individual's utility function is bounded. Finally, I suggest that the welfare functions traditionally used in climate economics are ill-equipped to deal with climate catastrophes in which population size changes. Drawing on recent work in population ethics I propose an alternative welfare framework with normatively desirable properties, which has the effect of dampening the contribution of catastrophes to welfare."